OTX2 mutations contribute to the otocephaly-dysgnathia complex. Issue 6 (10th May 2012) - Chassaing, Nicolas; Sorrentino, Susanna; Davis, Erica E; Martin-Coignard, Dominique; Iacovelli, Anthony; Paznekas, William; Webb, Bryn D; Faye-Petersen, Ona; Encha-Razavi, Férechté; Lequeux, Leopoldine; Vigouroux, Adeline; Yesilyurt, Ahmet; et al.
Abstract : Background: Otocephaly or dysgnathia complex is characterised by mandibular hypoplasia/agenesis, ear anomalies, microstomia, and microglossia; the molecular basis of this developmental defect is largely unknown in humans. Methods and results: This study reports a large family in which two cousins with micro/anophthalmia each gave birth to at least one child with otocephaly, suggesting a genetic relationship between anophthalmia and otocephaly. OTX2, a known microphthalmia locus, was screened in this family and a frameshifting mutation was found. The study subsequently identified in one unrelated otocephalic patient a sporadic OTX2 mutation. Because OTX2 mutations may not be sufficient to cause otocephaly, the study assayed the potential of otx2 to modify craniofacial phenotypes in the context of known otocephaly gene suppression in vivo. It was found that otx2 can interact genetically with pgap1, prrx1, and msx1 to exacerbate mandibular and midline defects during zebrafish development. However, sequencing of these loci in the OTX2-positive families did not unearth likely pathogenic lesions, suggesting further genetic heterogeneity and complexity. Conclusion: Identification of OTX2 involvement in otocephaly/dysgnathia in humans, even if loss of function mutations at this locus does not sufficiently explain the complex anatomical defects of these patients, suggests the requirement for a second genetic hit. Consistent with this notion, trans suppression of otx2 and other developmentally related genes recapitulate aspects of the otocephaly phenotype in zebrafish. This study highlights the combined utility of genetics and functional approaches to dissect both the regulatory pathways that govern craniofacial development and the genetics of this disease group.